Small change for Stuart - Evans, Lissa ca. 20. Jh (Corgi Books, 2012)
Stuart Horten - ten years old and small for his age - moves to the dreary town of Beeton, far away from all his friends. And then he meets his new next-door neighbours, the unbearable Kingley triplets, and things get even worse. But in Beeton begins the strangest adventure of Stuart's life as he is swept up in quest to find his great-uncle's lost workshop - a workshop stuffed with trickery and magic. There are clues to follow and puzzles to solve, but what starts as fun ends up as danger, and Stuart begins to realize that he can't finish the task by himself ... This is the first children's novel by Lissa Evans. This is a fast-moving blend of comedy and magic